Profil Literasi Sains Siswa Melalui Pembelajaran IPA Berbasis Pacu Jalur Kuantan Singingi - A. Rahmawati. P; Andika Febrian; Insih Wilujeng; Suyanta Suyanta; Sri Rejeki (Postgraduate, University of Mataram, 2023)
This study aims to determine the scientific literacy ability profile of students through science learning based on the Pacu Jalur Kuantan Singingi. This type of research is a quantitative descriptive research. The subjects of this study were students of class VIII SMP Negeri 3 Depok, Yogyakarta. The data collection technique used scientific literacy questions in the form of multiple choices totaling 5 items. The results showed that 67% of the indicators identified scientific facts or information were in the high category, the indicators analyzed data were 84% in the very high category, the indicators identified 100% of the scientific aspects in the very high category, the indicators justified the data 72% were in the medium category and the indicators provided arguments in a logical manner. scientific 94% with very high category.